Air pollution and coronary vasomotor disorders in patients with myocardial ischemia and non-obstructive coronary arteries. (3rd October 2022) - Camilli, M; Russo, M; Rinaldi, R; Iannaccone, G; Del Buono, M G; Lavecchia, G; Crea, F; Montone, R A
Abstract: Background: Coronary vasomotor abnormalities are an important cause of myocardial ischemia in patients with non-obstructive coronary artery disease (NOCAD). However, the role of air pollution in determining vasomotor disorders has never been investigated. Purpose: In this study, we evaluated the association between long-term exposure to particulate matter (PM) PM2.5 and PM10 and coronary vasomotor disorders in NOCAD patients. Methods: Patients with myocardial ischemia and NOCAD undergoing intracoronary provocative test with acetylcholine (ACh) were prospectively enrolled. The test was considered positive for epicardial coronary spasm in the presence of focal or diffuse epicardial coronary diameter reduction ≥90% in comparison with the relaxed state following intracoronary nitroglycerin administration given to relieve the spasm, associated with the reproduction of the patient's symptoms and ischaemic ECG shifts. Both patients with chronic myocardial ischemia (INOCA) and myocardial infarction with non-obstructive coronary arteries (MINOCA) were enrolled. Based on each case's home address, exposure to PM2.5 and PM10 was assessed. Only patients with >2 years of available data on air pollution exposure prior to coronary angiography were included. Results: We enrolled 287 patients (median age 62.0 years [52.0–70.0], 149 [51.9%] males): 161 (56.1%) INOCA and 126 (43.9%) MINOCA. One hundred seventy-six patients (61.3%) had positive provocative test. Exposure to PM2.5 (Figure 1) and PM10 was higher in patients with a positive provocative test (p<0.001). PM2.5 and PM10 were independent predictors of a positive coronary provocative test after adjustment for confounders. Interestingly, among patients with a positive provocative test, PM2.5 and PM10 were both independent predictors of MINOCA (p<0.001 and p=0.001, respectively; Figure 2) as clinical presentation, while only PM2.5 was independently associated with the occurrence of epicardial spasm as opposed to microvascular spasm (p<0.001). Conclusions: We provide novel insights into the missing link between air pollution and ischemic heart disease. In particular, higher exposure to air pollution in patients with myocardial ischemia and NOCAD is associated with coronary vasomotor abnormalities, and PM2.5 is an independent risk factor for the occurrence of epicardial spasm and for MINOCA as clinical presentation. Funding Acknowledgement: Type of funding sources: None.